A A Novel Layered System to Prevent High-Energy, Ionizing Radioactive Photon Transmissions and Control Particle Behavior With The Utilization of Monte Carlo Transport Modeling Via SPENVIS-Based Modular Implementation - Noon, Daniel (JOURNAL OF ADVANCES IN PHYSICS, 2018)
Today, mass nuclear weapons and reactor plants are becoming more prominent. However, current methods of radiation shielding are not viable due to heavy cost and ineffective means of weakening photon momentum. Therefore, it becomes necessary to design structures resistant to the behavior of radiation from exposing to human life. Specifically, 280 computational experiments were conducted in a SPENVIS environment utilizing Multi-Layered Shielding Simulation (MULASSIS) and Geant4 Radiation Analysis for Space (GRAS) on multiple shielding models. These thirteen models tested against nuclear, artificially-generated incident particles under single and multi-ray analyses with four angular photon distributions in comparison to SHEILDOSE, a current standard for cosmic radiation shielding developed by the European Space Agency. These designs using stainless steel, lead, slightly-radioactive bismuth, and lithium-hydride prevented over 99% of particle detection compared to SHIELDOSE, which conversely increased the neutron-energy dose by over 700%, and insufficiently reduced high-energy gamma ray penetration. Per kilogram, my model is 144 times cheaper and only a small fraction of the thickness of either SHIELDOSE or metal foams. Thus, the potential of enhanced nuclear plants, further space exploration, and an overall safer approach to utilizing or preventing exposure to atomic particles such as with multi-disaster protection buildings can become more readily available, thus saving millions of lives that are in impending danger.